Ambient air pollutant PM10 and risk of pregnancy-induced hypertension in urban China. (August 2015) - Huang, Xin; Qiu, Jie; Zhang, Yaqun; Qiu, Weitao; He, Xiaochun; Wang, Yixuan; Sun, Qingmei; Zhao, Nan; Cui, Hongmei; Liu, Sufen; Tang, Zhongfeng; Chen, Ya; et al.
Abstract Background: The relationship between air borne particulate matter ≤10 μm (PM10) exposure and pregnancy-induced hypertension (PIH) is inconclusive. Few studies have been conducted, and fewer were conducted in areas with high levels of PM10. Methods: To examine the association between PM10 and PIH by different exposure time windows during pregnancy, we analyzed data from a birth cohort study conducted in Lanzhou, China including 8 745 pregnant women with available information on air pollution during pregnancy. A total of 333 PIH cases (127 gestational hypertension (GH) and 206 preeclampsia (PE)) were identified. PM10 daily average concentrations of each subject were calculated according to the distance between home/work addresses and monitor stations using an inverse-distance weighting approach. Results: Average PM10 concentration over the duration of entire pregnancy was significantly associated with PIH (OR = 1.12, 95%CI: 1.02, 1.23 per 10 μg m−3 increase), PE (OR = 1.16, 95%CI: 1.03, 1.30 per 10 μg m−3 increase), late onset PE (OR = 1.17, 95% CI: 1.03, 1.32 per10 μg m−3 increase), and severe PE (OR = 1.25, 95% CI: 1.06, 1.48 per 10 μg m−3 increase). Average PM10 during the first 12 gestational weeks was associated with the risk of GH (OR = 1.10, 95% CI: 1.00, 1.21 per 10 μg m−3 increase), and PM10 exposure before 20 gestational weeks was associated with the risk of severe PE (OR = 1.14, 95% CI: 1.01, 1.30 per 10 μg m−3 increase). Conclusions: We found that high level exposure to ambient PM10 during pregnancy was associated with an increased risk of PIH, GH and PE and that the strength of the association varied by timing of exposure during pregnancy.